Aspectos jurídicos do marco regulatório do pré-sal sob a luz da política nacional sobre mudança do clima. - Silva, Ana Claudia Ribeiro Cardoso da (2014)
The present dissertation had with main objective to analyse the regulatory framework of the pre ¿salt the light of national policy on climate change, identifying whether there are points of confronting between the two legal frameworks. Therefore, it was necessary to demonstrate the evolution of environmental law in the world and in Brazil, as well as the institutionalization of climate protection policy in Brazil, their policies and objectives. In the oil industry sector, evaluate the influence of owning countries and oil producers in the Brazilian energy matrix, the legal changes that have altered the ownership of natural resources throughout history, the change of legislation for oil exploration in the pre -salt field in 2010, and the current scenario of oil exploration in the polygon. In order to achieve the proposed goal, there was a brief overview on the scientific aspects of climate change and the voluntary commitments made by Brazil, in an effort to reduce gas emissions between 36,1 % to 38,9 % by 2020. It was found that oil is a finite resource and that, according to the theory of Peak Oil and the current target for oil exploration in the pre-salt, there are two possible future scenarios with different consequences to Brazil. It was understood that the country published two legislations, one of climate protection and other oil exploration in the pre-salt, which does not establish a dialogue and demonstrate a route of confront between the policies. Still, proposals were searched for confronting of the two scenarios mentioned above.